DIGITAL BRANDING PT AGRODANA FUTURES DALAM MEMBANGUN CITRA SEBAGAI PENYEDIA LAYANAN PERDAGANGAN BERJANGKA TERPERCAYA: STUDI PADA KONTEN MEDIA SOSIAL - Cindy Januaristin Suryani; Supriyono Supriyono (STKIP Pesisir Selatan, 2025)
The futures trading industry in Indonesia faces challenges related to public trust due to high investment risks and illegal brokerage practices. This condition encourages futures brokerage companies to build a credible and trustworthy image, one of which is through a digital branding strategy. This study aims to analyze how PT Agrodana Futures constructs digital branding as a trusted futures trading service provider through social media content. This study uses a qualitative approach with active participation observation, where the researcher is directly involved in the company's digital marketing activities during a certain period. The analysis focuses on the messages, communication style, brand identity consistency, and trust narratives built in the company’s digital content. The results show that PT Agrodana Futures builds its digital branding through the presentation of educational content, data-based market analysis, affirmation of the company's legality, consistency in visual identity and communication across various digital platforms. The narrative of trust is not created through exaggerated promotional claims, but rather through information transparency, the presence of professional analysts, and the highlighting of the company's achievements and awards. The digital branding implemented functions not only as a marketing strategy but also as a means of building public trust in the futures trading industry.